ANALISIS MOTIVASI KERJA PADA KARYAWAN DIVISI TEKNIK PT ASURANSI CENTRAL ASIA CABANG DUTA MERLIN JAKARTA - Indra Sapri; Ana Septia Rahman (Journal of Research and Publication Innovation, 2024)
Employees are a very important human resource for the company because they have a role as drivers of all company activities. To achieve company goals, quality human resources are needed who can integrate the company's vision. To maintain employee work productivity, enthusiasm and motivation are needed as encouragement. Motivation is a force that results from a person's desire to satisfy their needs. Employees fulfill their desires by working. This research uses qualitative descriptive research. The subjects in this research were employees of the engineering division of PT Asuransi Central Asia KCU Duta Merlin. The data collection methods in this research are observation, interviews, and documentation. The results of this research are (1) employees in this division show high productivity and good quality work. The work motivation implemented, such as bonuses and overtime pay for certain achievements, has encouraged employees to work with high enthusiasm and discipline. Personal development programs also make a positive contribution to performance, by enabling employees to improve their technical abilities and professionalism. (2) One of the main obstacles is the lack of variety in the motivation programs offered by companies. While overtime pay and bonuses are appreciated, variations in rewards and incentives can further enrich an employee's motivational experience.